INTERAKSI SOSIAL ORANG TANAH TORAJA PADA MASYARAKAT LOKAL DI KABUPATEN KOLAKA - Dewi Anggraini (Universitas Muhammadiyah Sidoarjo, 2013)
Tanah Toraja tribe community who came to nickel mining in Maniang Island are from five regions in Tanah Toraja areas such as Mamasa, Baruppu, Buakayu, Makale, and Mengkendek, who eventually settled in Pomalaa, Kolaka district and interact with the local population Tolaki Mekongga. Interaction between migrant communities (Tator Tribe) and local the key of all social life that occurs in communities (Tolaki Tribe) of mining area, Pomalaa. The purpose of this study is to determine the interaction of Tanah Toraja people in Tolaki Mekongga society and to know the local culture support in the welcoming of Tanah Toraja Society in Kolaka. This study uses qualitative method with phenomenological approach, in which the data collection method uses the participant observation and in-depth interviews by setting informants. The results of social interaction between Tator people and local communities basically run well, although sometimes hidden conflicts appear on the Tolaki Mekongga as local ethnic favoritism Tator in everyday life who are likely to be exclusive and luxurious, especially in the traditional rituals.